Handover adaptation for load balancing scheme in femtocell Long Term Evolution (LTE) network / Mohammad Taufik Mohd Nasir - Mohd Nasir, Mohammad Taufik (2014)
Long Term Evolution (LTE) Network is the latest network technology before the presence of Advanced-LTE (LTE-A). LTE is introduced by 3rd Generation Partnership Project (3GPP) LTE to improve the mobile phone standard to cope with future technology evolutions and needs. Recently, Femtocell which known as Home NodeB (HNB) is the remarkable technology network that implanted in the LTE network in order to fulfill the upcoming demand of high data rates. However, as the User Equipment (UE) is allowed to move freely with different network it because changed in handover rate and hence, probability of drop call increased. In addition, different speed of UE also affects the number of handover and drop call rate. This paper analyzed on the load balancing scheme based on performance of handover and dropped call rate with different number of UE and different speed of the UE. The scheme requests Femtocell which deployed into Macrocell based on velocity ofUE by considering the number of UE. The handover procedures is determined by using simulation based on the number of UE and UE velocity. The simulation results show a significant improvement in term of handover and drop call rates and enhanced better performance of Femtocell in LTE network.